PENGARUH LINGKUNGAN KERJA, KEPUASAN KERJA, DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA PABRIK GULA MERITJAN KEDIRI - Shinta Ayu Eriana; Edwin Agus Buniarto; Zulfia Rahmawati; Agus Hariyanto (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Employee performance is very important in a company to achieve its goals. If the performance of employees is less than the maximum in the company it will affect several success factors that support employee performance. Some factors that support the success of employee performance are a work environment that is increasingly uncomfortable, job satisfaction within the company is not good, and also the employee's morale decreases when doing a job. This study aims to determine the effect of the work environment, job satisfaction, and work morale on employee performance at the Meritjan Kediri Sugar Factory. The sampling method uses simple random sampling, and the sampling technique is based on the table determining the number of ISSAC and Michael samples from a population of 135 employees in 2019, with an error rate of 10% obtained as many as 92 employees at the Meritjan Kediri Sugar Factory. The data collected were analyzed using multiple linear regression analysis assisted with SPSS 16. The results of multiple regression analysis showed the equation Y = 4.682 + 0.177X1 + 0.404X2 + 0.147X3 which means that the work environment variables significantly influence employee performance with a regression coefficient of 0.177, job satisfaction has an effect significant to employee performance with a regression coefficient of 0.404. While the variable morale has a significant effect on employee performance with a regression coefficient of 0.147. Meanwhile, the results of the analysis conducted showed that the work environment (), job satisfaction () and morale () had significant and significant effects on employee performance (Y), and had a Determination Coefficient or R Square of 0.373 or 37.3%.